The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/gh-70-63-2015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of terracettes on the surface hydrology of steep-sloping and subalpine environments: some preliminary findings

Abstract: Abstract. Alpine and mountain slopes represent important pathways that link high-altitude grazing areas to meadows and rangelands at lower elevations. Given the often acute gradients associated with such environments, they potentially represent highly efficient runoff conveyance routes that facilitate the downslope movement of runoff and associated material during erosion events. Many such slopes host series of small steps, or "terracettes". The juxtaposition of terracettes against the natural downslope flow p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
2
7
0
1
Order By: Relevance
“…We observed less vegetative cover on benches than risers, which contradicts the findings of Greenwood et al (2015) but is supportive of our observed negative correlation between θ v and vegetative cover shown in Fig. 6 and the observations of terracette conditions as described by Rahm (1962) and Radcliffe (1968).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…We observed less vegetative cover on benches than risers, which contradicts the findings of Greenwood et al (2015) but is supportive of our observed negative correlation between θ v and vegetative cover shown in Fig. 6 and the observations of terracette conditions as described by Rahm (1962) and Radcliffe (1968).…”
Section: Discussionsupporting
confidence: 84%
“…Locally, soil moisture can be spatially highly variable (Western et al, 2002), play a critical role in the rainfall–runoff response of catchments (Dunne et al, 1991), and serve as an ecological driver controlling plant transpiration and, particularly in semiarid lands, acting as the dominant control affecting the structure, function, and diversity of an ecosystem (Robinson, 2008). It is recognized that conditions such as antecedent moisture play a substantive role in hillslope runoff and erosion (Castillo et al, 2003) alongside slope (Liu and Singh, 2004) and surface morphology (Bergkamp, 1998; Thompson et al, 2010), which often necessitate some parameterization of topography in hydrologic models (Gerke et al, 2010; Harpold et al, 2010; Greenwood et al, 2015). However, because of limitations in the spatial resolution of topographic data and computational resource demands (Tesfa et al, 2011), hydrologic models often do not account for microtopography (soil surface variations of <1m vertical relief as described by Moser et al, 2007), despite a general recognition that influences of microtopography on soil moisture in semiarid ecosystems can increase the precision of the variables used in modeling the processes of surface runoff and sediment transport (Jones et al, 1996; Savabi, 2001; Mapfumo et al, 2004; Easton et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome of this work has allowed them to predict spatial and temporal variations of permafrost in sensitive mountain environments under a range of ongoing and future climate change scenarios. Greenwood et al (2015) combine GIS-based and experiment-based approaches to assess the influence of hillslope terracettes on surface hydrology on steep-sloping and subalpine terrain. Their work highlights the fact that the spatial heterogeneity of these relatively common features means that they can influence the surface hydrology in ways that can be both positive and negative.…”
mentioning
confidence: 99%